2013
DOI: 10.1126/science.1231031
|View full text |Cite
|
Sign up to set email alerts
|

PINK1-Phosphorylated Mitofusin 2 Is a Parkin Receptor for Culling Damaged Mitochondria

Abstract: Senescent and damaged mitochondria undergo selective mitophagic elimination through mechanisms requiring two Parkinson’s disease factors, the mitochondrial kinase PINK1 and the cytosolic ubiquitin ligase Parkin. The nature of the PINK-Parkin interaction and identity of key factors directing Parkin to damaged mitochondria are unknown. We show that the mitochondrial outer membrane GTPase mitofusin (Mfn) 2 mediates Parkin recruitment to damaged mitochondria. Parkin bound to Mfn2 in a PINK1-dependent manner; PINK1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
1,046
1
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,118 publications
(1,083 citation statements)
references
References 24 publications
31
1,046
1
5
Order By: Relevance
“…MFN2 plays a central role in autophagy induction in the liver (Biel et al., 2016), skeletal and cardiac muscle (Chen & Dorn, 2013; Sebastián et al., 2012). Our findings here not only provide mechanistic correlation of SIRT1‐MFN2 axis in autophagy regulation in the liver but also explain why aged livers are intrinsically vulnerable to ischemic stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MFN2 plays a central role in autophagy induction in the liver (Biel et al., 2016), skeletal and cardiac muscle (Chen & Dorn, 2013; Sebastián et al., 2012). Our findings here not only provide mechanistic correlation of SIRT1‐MFN2 axis in autophagy regulation in the liver but also explain why aged livers are intrinsically vulnerable to ischemic stress.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, pathologically low levels of MFN2 may adversely affect the delivery of autophagosomes to lysosomes, as MFN2 may be involved in the fusion between the autophagosome and the lysosome through its interaction with the Ras‐related protein Rab7 (Zhao et al., 2012). On the other hand, as MFN2 ubiquitination by PTEN‐induced kinase 1(PINK1) serves as a mitophagy signal for identifying and clearing damaged mitochondria (Chen & Dorn, 2013), depletion of MFN2 during I/R could prevent PINK1‐associated mitophagy in old livers. Noticeably, I/R also significantly decreased MFN1 expression in old hepatocytes (Figure S4A).…”
Section: Discussionmentioning
confidence: 99%
“…Loss of the mitochondrial membrane potential triggers PINK1 accumulation on the surface of mitochondria and phosphorylates mitochondrial outer membrane proteins 49, 53. This process accelerates Parkin translocation from the cytosol to the mitochondria,49, 54 and thus ubiquitinates mitochondrial outer membrane proteins to promote recruitment of an autophagosome 55. Other than the PINK1/Parkin pathway, BNIP3, BNIP3L and FUNDC1 are also emerging key players in the regulation of mitophagy 13, 56, 57.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Pink1 phosphorylates Miro and participates in mitochondrial depolarization 23 . Pink1 phosphorylates Mfn2 and mediates mitochondrial degradation 24 . Pink1 binds and colocalizes with TRAP1 in the mitochondria.…”
Section: Pink1 Inhibits Mitochondrial Fragmentation and Apoptosismentioning
confidence: 99%